Historical empathy scale-adult form: A study on validity and reliability - Çalışkan, Alperen; Yıldırım, Yusuf; Çalışkan, Hüseyin (My University, 2023)
The purpose of this study is to develop a valid and reliable measurement tool to identify the historical empathy tendencies of adults including cognition, affect, and behaviour dimensions by treating the individual as a whole. In this study, where four different study groups were used, each group was determined by the convenience sampling method, one of the purposive sampling methods. The study group consisted of 1132 adult individuals living in different parts of Turkey. The study group consisted of 322 adults for Exploratory Factor Analysis (EFA), 381 adults for Confirmatory Factor Analysis (CFA), and 356 adults for criterion-related validity studies of the scale. In addition, the study group for test-retest reliability consisted of 73 individuals studying at the faculty of education of a state university in the Marmara region. At the end of the Exploratory Factor Analysis, a 16-Item measurement tool consisting of three sub-factors, namely "cognition", "affect”, and "behaviour", explaining 57.25% of the total variance was obtained. The Internal Consistency Reliability Coefficient calculated for the whole scale was calculated as .88, .85 for the first factor, .82 for the second factor and .80 for the third factor. The Test-Retest Reliability Coefficient of the scale was found to be .77, .72 for the first factor, .73 for the second factor and .70 for the third factor. It was determined that the Item-total correlations of the subscales ranged between .48 and .62 and all the differences between the means of the upper and lower 27% groups were significant. In conclusion, it is concluded that the "Historical Empathy Scale-Adult Form" developed to identify the historical empathy tendency levels of adult individuals is a valid and reliable scale as it meets the psychometric criteria of scale development studies to a good extent. The scale, which is observed to be in line with the theoretical structure of the concept of empathy, consists of three dimensions: cognitive, behavioural, and affective. Using this developed scale, relational studies can be conducted in order to identify the historical empathy tendencies of adult individuals or to explain them with related concepts.